ANALISIS PENGELOLAAN PARIWISATA KAMPUNG WISATA SENTANA KELURAHAN TANJUNG SEKAYAM KECAMATAN KAPUAS KABUPATEN SANGGAU - Iis Sarlina; Bambang Genjik; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This research aims to analyze the tourism management of Sentana Tourism Village in Tanjung Sekayam Village, Kapuas District, Sanggau Regency. The research method used is a descriptive method with a qualitative approach. The source of data in this research is the community managing the tourism village of Sentana tourism which consists of 10 people as respondents . Data collection was obtained through interview guidelines, analyzed through data reduction, data presentation and verification/drawing conclusions, then checking the validity of the data using triangulation techniques. Researcher conducted research and interview 3 times. The results show that tourism management supported by the local government can make the Sentana tourist village as a local tourist spot that attracts local and non-local tourists and is used as a place to hold events which are held three times a year, every April 4th , after the celebration of Eid Al-Fitr and every end of the year before the New Year celebrations , the provision of grant funds to POKDARWIS is used to promote the Sentana Tourism Village and organize various events . Supporting facilities for opening a business such as carts for selling booths, rickshaws, construction of water fronts and open areas such as green land. Keywords: Management, Sentana Tourism Village